The Origins of Totalitarianism - Arendt, Hannah 1906-1975 (New York Harcourt, 1973)
Generally regarded as the definitive work on totalitarianism, this book is an essential component of any study of twentieth-century political movements. Arendt was one of the first to recognize that Nazi Germany and the Soviet Union were two sides of the same coin rather than opposing philosophies of Right and Left. & With the Origins of Totalitarianism Hannah Arendt emerges as the most original and profound-therefore the most valuable-political theoretician of our times.
Pt. 3. Totalitarianism. A classless society ; The totalitarian movement ; Totalitarianism in power ; Ideology and terror : a novel form of government.
Bibliography: p. [483]-507.
New edition with added prefaces
Keywords: Politics; Philosophy; Antisemitism; Imperialism; Tourist Guide